Scoring systems for prediction of mortality in decompensated liver cirrhosis: A meta-analysis of test accuracy - Wu, Shi-Lan (World J Clin Cases, 2018)
AIM: To compare the accuracy of the scoring systems Child-Turcotte-Pugh (CTP), Model for End-stage Liver Disease score (MELD), MELD-Na, and MELD to Serum Sodium ratio (MESO) to predict the mortality in decompensated liver cirrhosis. METHODS: The PubMed, Web of Science, Cochrane Library, EMBASE, and Ovid databases were systematically searched from inception to September 2018 for relevant articles, and we evaluated the quality of the included studies. The accuracy of scoring systems was analyzed with Stata 12 and MetaDiSc 1.4. RESULTS: Sixteen studies involving 2337 patients were included. The pooled areas under the summary receiver operating characteristic curves (AUROCs) of CTP, MELD, MELD-Na, and MESO to predict mortality were 0.81, 0.78, 0.85, and 0.86, respectively. Within 3 mo, the AUROCs of CTP, MELD, and MELD-Na in predicting mortality were 0.78, 0.76, and 0.89, respectively. The AUROCs of CTP, MELD, and MELD-Na at 3 mo were 0.86, 0.78, and 0.86, respectively. The AUROCs of CTP, MELD, and MELD-Na at 6 mo were 0.91, 0.83, and 0.90, respectively. The AUROCs of CTP, MELD, and MELD-Na at 12 mo were 0.72, 0.75 and 0.84, respectively. In cirrhotic patients with bleeding, the AUROCs of CTP and MELD were 0.76 and 0.88, respectively. CONCLUSION: MESO has the highest AUROC in all assessed scoring systems. Considering the different time points, MELD-Na has good accuracy in predicting the mortality of decompensated liver cirrhosis. Compared to CTP, MELD is better in predicting variceal bleeding.